Identification of a novel hybrid sterility locus S67 between temperate japonica subgroup and basmati subgroup in Oryza sativa L - Yonggang Lv; Jing Li; Ying Yang; Qiuhong Pu; Jiawu Zhou; Xianneng Deng; Yu Zhang; Dayun Tao (Scientific Reports)
Abstract Asian cultivated rice (Oryza sativa L.) is the most important cultivated species in the AA genome species of the genus Oryza. basmati is a special and famous subgroup in Asian cultivated rice, and temperate japonica is one of the most important cultivated subgroup, too. However, hybrid sterility hinders the introgression of favorable traits and the utilization of hybrid vigour between the two subgroups. The genetic basis of intraspecific hybrid sterility between temperate japonica and basmati remained elusive. In this study, a novel hybrid sterility locus S67 was identified, which caused hybrid male sterility in hybrids between the temperate japonica rice variety Dianjingyou 1 (DJY1) and the basmati rice variety Dom-sufid. Initial mapping with BC1F1, BC4F1, BC4F2 populations and DNA markers located S67 between RM5362 and K1-40.6 on the long arm of chromosome 1. Genetic analysis confirmed that S67 caused a transmission advantage for the temperate japonica rice S67-te allele in the hybrid offsprings. This result not only fills the gap in the research on hybrid sterility between basmati and temperate japonica, but also lays a good foundation for the systematic study of the genetic nature of hybrid sterility between basmati and other subgroups, as well as the full exploration and utilization of this subgroup through the creation of wide or specific compatibility lines to overcome hybrid sterility. In addition, this result can also help us broaden our understanding of genetic differentiation within Asian cultivated rice and hybrid sterility between inter-subgroups.